Architecture of Hardware and Software for Unidirectional Data Transmission in Computer Networks - Y. I. Varatnitski; R. A. Rumas (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of a study of the architecture of hardware and software for unidirectional data transmission in computer networks are presented. The architecture is presented in the form of optical galvanic isolation, media converters and proxy servers, excluding bidirectional data transmission at the hardware level. Work on unidirectional data transmission is carried out on the basis of the UDP transport protocol, which provides operation without establishing bidirectional interaction. Unidirectional data transfer is carried out by a proxy server running a special sender’s software that performs unidirectional data file transfer. This software converts the source data file into a unidirectional stream of UDP datagrams. To receive a unidirectional stream of UDP datagrams, a proxy server is used, on which the recipient’s special software is running. The receiving proxy server receives, processes and generates the source data file. The reliability of the unidirectional transmission of data files is ensured by redundancy (multiple transmission) and checksum verification.